COLD, HARD JUSTICE LESSONS FROM THE FLEET: INNOVATING FROM THE BOTTOM UP - Ha-Redeye, Omar (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
With law school graduates encountering increased difficulty in securing articling positions, legal incubators are an alternative way of providing practical training and mentorship opportunities for young practitioners. Not only do they have the potential to help launch careers in law, but they can also play a major role in increasing access to justice. Though legal incubators have been gaining popularity in law schools across the United States, they are still a novel concept in Canada. This article discusses the resources and practice models used by Fleet Street Law, a law practice in Toronto that evolved into the first legal incubator in Canada. The use of innovative business models allowed for greater service of low income and marginalized populations, especially on a “low-bono” rate, and also assisted in providing essential supports for racialized and minority lawyers early in their career. The flexible and innovative nature of a legal incubator was beneficial for the purposes of experimentation, but there were challenges associated with cost and long-term participation. The model of a practitioner-based incubator, as an alternative to traditional-type clinics, should be strongly considered by law schools to help address some of the market needs in the legal community today.